'Stary doktor' — the old doctor — Janusz Korczak. (4th April 2011) - Cieslak, W T; Williams, A N
Abstract : Few paediatricians have heard of Janusz Korczak (Dr Henryk Goldszmit) (1878–1942) even though he was a pioneer on children's rights and child healthcare. Korczak devoted his life to children and their welfare. He was a children's physician, child advocate, educator, and psychologist. He was also an early radio broadcaster under the name the ' Stary Doktor' ('The Old Doctor'), celebrated children's writer and playwright. Korczak wrote one of the earliest Children's Charters. He also regularly defended children and their rights in juvenile courts and, most notably, in 1927 Stanislaw Lampisz, a juvenile accused of shooting dead his headmaster. Korczak spoke of the need for a Declaration of Children's Rights long before any such document was drawn up by the United Nations in the UN Convention on the Rights of the Child (1989). Korczak's final years were spent running a children's home in the Warsaw Ghetto during the German occupation in World War Two. In August 1942, he and the children under his care were marched to the railway station for transportation for 'resettlement'. Although recognised and given the opportunity to save himself, Korczak stated 'One does not leave a sick child – my place is with them … ' He and the children were taken to Treblinka – an extermination camp. No one survived. In all, Korczak authored more than 20 books, including children's fiction, pedagology and posthumously published Pamietnik (diary). This presentation will relate Korczak's life and work within the historical context of early 20th century Europe and his ongoing relevance to worldwide present and future child healthcare. Excerpts from his writings including the celebrated children's novel ( Król Macius Pierwszy ) King Matt the First (1923) – regarded by many as one of the finest children's books ever written – will be given during this presentation. Janusz Korczak and the events of his time still have much to teach us.